Examining the Effects of Feedback Accuracy and Timing on Skill Acquisition. Issue 1 (2nd April 2020) - Brand, Denys; Novak, Matthew D.; DiGennaro Reed, Florence D.; Tortolero, Samara A.
ABSTRACT: Feedback involves providing information about past performance and indicating how to improve future performance. Although the literature contains numerous examples of feedback as an effective method for improving performance across a range of organizational settings, much remains unknown about the specifics of how feedback acts to change behavior. This study evaluated the combined effects of feedback accuracy (100%, 80%, 20%) and timing (feedback following each trial or after a block of 25 trials) on skill acquisition in undergraduate students when presented with a computerized match-to-sample task that required participants to learn the names of shapes. Results reveal that feedback accuracy had a significantly greater effect on performance than the timing of the feedback.